Analysis of the Effect of Health Service Quality on Public Trust and Satisfaction - I'in Alfiah; Hari Karyadi; Suji Suji (Eduvest - Journal of Universal Studies, 2025)
This research is intended to determine and explain the effect of health service quality on public trust and satisfaction (study at the Community Health Center Rogotrunan Lumajang Sub-District Lumajang Regency). This research uses a quantitative approach and is classified as explanatory research. The data collection technique used was a questionnaire. The population in this study was the entire population of Lumajang District, Lumajang Regency who used health services at the Rogotrunan Community Health Center, Lumajang Sub-District, Lumajang Regency. The research sample was determined as 100 respondents and the determination of respondents as samples used a simple random sampling method. The data analysis used to path analysis with a multiple linear regression approach which is analyzed with the Statistical Package for the Social Sciences (SPSS) software package. The results of the research show that there is an effect of service quality on public trust in the Rogotrunan Lumajang Sub-District Lumajang Regency. There is an effect of service quality on public satisfaction at the Rogotrunan Lumajang Sub-District Lumajang Regency. There is an effect of public trust on public satisfaction at the Rogotrunan Lumajang Sub-District Lumajang Regency. And, there is an effect of service quality on public satisfaction at the Rogotrunan Lumajang Sub-District Lumajang Regency through intervening public trust.